Menjembatani Jarak: Komunikasi Interpersonal dalam Hubungan Orang Tua-Anak di Pesantren - Ernita Arif; Rahmi Surya Dewi (Society, 2025)
This study aims to examine the forms of interpersonal communication between parents and children in fostering emotional closeness within the environment of Pondok Pesantren Sumatera Thawalib Parabek, Bukittinggi, West Sumatra. The research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with parents and students at the Islamic boarding school. The findings indicate that interpersonal communication through digital media, including telephone calls, text messaging, video calls, sending packages, and direct visits, plays an important role in maintaining emotional bonds between parents and children. However, the quality of communication characterized by empathy and openness was found to be more influential than communication frequency. Religious values, Minangkabau local culture, and pesantren traditions also shape supportive communication patterns that emphasize respect for authority. Effective interpersonal communication can strengthen students’ emotional stability during their educational experience in the pesantren. These findings are expected to contribute to the development of family communication literacy and provide practical insights for pesantren institutions in supporting healthy parent–child relationships.